The duke and the stars : astrology and politics in Renaissance Milan - Azzolini, Monica, 1971- (I Tatti studies in Italian Renaissance history., 2013)
The Duke and the Stars explores science and medicine as studied and practiced in fifteenth-century Italy, including how astrology was taught in relation to astronomy. It illustrates how the 'predictive art' of astrology was often a critical, secretive source of information for Italian Renaissance rulers, particularly in times of crisis.